Isolation and characterization of onion degrading bacteria from onion waste produced in South Buenos Aires province, Argentina - Rinland, Maria Emilia (2015)
Onion production in Argentina generates a significant amount of waste. Finding an effective method to recycle it is a matter of environmental concern. Among organic waste reuse techniques, anaerobic digestion could be a valuable alternative to current practices. Substrate inoculation with appropriate bacterial strains enhances the rate-limiting step (hydrolysis) of anaerobic digestion of biomass wastes. Selection of indigenous bacteria with the ability to degrade onion waste could be a good approach to find a suitable bioaugmentation or pretreatment agent. We isolated bacterial strains from onion waste in different degradation stages and from different localities. In order to characterize and select the best candidates, we analyzed the growth patterns of the isolates in a medium prepared with onion juice as the main source of nutrients and we evaluated carbon source utilization. Nine strains were selected to test their ability to grow using onion tissue and the five most remarkable ones were identified by 16S rRNA gene sequencing. Strains belonged to the genera Pseudoxanthomonas, Bacillus, Micrococcus and Pseudomonas. Two strains, Bacillus subtilis subsp. subtillis MB2-62 and Pseudomonas poae VE-74 have characteristics that make them promising candidates for bioaugmentation or pretreatment purposes.